الصعوبات التي تحد من إمكانية إعادة تقييم الأصول الثابتة دراسة ميدانية في الشركات المساهمة السورية - العليص, إبراهيم; عبود, نهى غانم (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول البحث الصعوبات التي تحد من إمكانية إعادة تقييم الأصول الثابتة في الشركات المساهمة السورية, ولتحقيق أهداف البحث قامت الباحثة باستخدام قائمة استقصاء تمّ توزيعها على عدد من المدراء الماليين ومراجعي الحسابات في الشركات المساهمة السورية, وكان من أهم نتائج البحث: -إن الطريقة الأفضل والمتبعة في تقييم الأصول الثابتة في الشركات المساهمة السورية المدروسة هي طريقة التكلفة. - هناك مجموعة من الصعوبات التي تحد من إمكانية إعادة تقييم الأصول الثابتة في الشركات المساهمة السورية أهمها: صعوبة توفير سوق منتظمة للأصول الثابتة بسبب عدم وجود أرقام قياسية متخصصة, وضعف التقدم التكنولوجي السريع في الآلات والمعدات, ارتفاع تكلفة إعادة تقييم الأصول الثابتة, عدم وجود مقيمين مهنيين ومحترفين, ضعف برامج التعليم المحاسبي في التعريف بمتطلّبات المحاسبي الدولي رقم (16), صعوبة فهم متطلبات المعيار المحاسبي الدولي وتفسيره رقم (16), إضافةً إلى قلة المعايير والضوابط التي تحكم عملية إعادة التقييم. This research deals with the difficulties that limit the possibility of revaluating fixed assets in the Syrian joint stock companies. To achieve the objectives of the research, the researcher have designed a questionnaire and asked a number of financial managers and auditors in the Syrian joint stock companies to fill it out. The most important results of the research are: - The best way used in the evaluation of fixed assets in the studied Syrian contributing companies is the cost method. - There is a range of difficulties that limit the possibility of applying the method of revaluation of fixed assets in the Syrian joint stock companies including: the difficulty of providing a regular market for fixed assets is due to the lack of specialized records, the weakness of rapid technological advances in machinery and equipment, the high cost of re-evaluation of fixed assets, the lack of professionals, the weakness of educational accounting programs that define the requirements of international Accounting Standard No. (16), the difficulty of understanding and interpretation of the requirements of international Accounting Standard No. (16), in addition to a lack of standards and regulations that govern the process of re-evaluation.